Histological Development of Thymus in Goat Embryo - Prasad, Madhav; Prakash, Ajay; Pathak, Archana; Farooqui, M M; Singh, S P (Indian Journal of Veterinary Anatomy, 2012)
At 16.87 days of gestation the thymic primordium of goat was observed on either side of developing pharynx, which chiefly contained eosinophilic and basophilic cells. In 20.62 days old embryo, the parenchyma of primordium had epithelial-reticular cells which were often arranged in concentric layers. At 24.37 days of gestation, the central part in the primordium of one embryo was chiefly consisted of epithelial-reticular cells and the peripheral part was formed by lymphoblasts, epithelial-reticular cells and few small sized lymphocytes. At few places epithelial palisades were observed in the parenchyma of thymic primordium. Several developing erythrocytes and congested blood vessels were found at the periphery of the primordium which was particularly abundant in 20.62 days old embryo.